Capacity Building for Small Fishermen Ds. Supervisor of Aluh Aluh District, Banjar Prov. South Kalimantan - Isra Ul Huda; Asruni Asruni; Anthonius Junianto Karsudjono (Penerbit Mandalika Indonesia, 2025)
The research